2011
DOI: 10.3102/0002831210384839
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Literacy and Science in Biology

Abstract: This study examined the effects of professional development integrating academic literacy and biology instruction on science teachers' instructional practices and students' achievement in science and literacy. The intervention consisted of 10 days of professional development in Reading Apprenticeship, an instructional framework integrating metacognitive inquiry routines into subject-area instruction to make explicit the tacit reasoning processes, problem-solving strategies, and textual features that shape lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(30 citation statements)
references
References 81 publications
2
23
0
2
Order By: Relevance
“…Therefore, we conclude that the success of our intervention for low-SES students of color is attributable to the integration of the inquiry-based learning cycle and reading and writing with direct and explicit vocabulary instruction that promotes students' science performance. Our findings are also consistent with previous studies on science and reading integration Greenleaf et al, 2011;Klenstchy, 2005;Shanahan & Shanahan, 2008;Wallace et al, 2004).…”
Section: Science Achievementsupporting
confidence: 95%
See 2 more Smart Citations
“…Therefore, we conclude that the success of our intervention for low-SES students of color is attributable to the integration of the inquiry-based learning cycle and reading and writing with direct and explicit vocabulary instruction that promotes students' science performance. Our findings are also consistent with previous studies on science and reading integration Greenleaf et al, 2011;Klenstchy, 2005;Shanahan & Shanahan, 2008;Wallace et al, 2004).…”
Section: Science Achievementsupporting
confidence: 95%
“…Hence, it stands to reason that advanced literacy skills can facilitate science learning. However, the amount of language-based activities is significantly reduced especially in secondary science classrooms due to teachers' lack of knowledge on how to integrate literacy instruction into hands-on scientific exploration (Author, 2012;Greenleaf et al, 2011;Rivard, 2004). As Shanahan and Shanahan (2008) advocated, the advanced literacy instruction should be embedded within content area classes as a focus for middle and high school settings, which is also the trend in science education reform (Hines, Wible, & Mccartney, 2010;Stoddart, Pinal, Latzke, & Canaday, 2002).…”
Section: A Randomized Study Of a Literacyintegrated Science Interventmentioning
confidence: 95%
See 1 more Smart Citation
“…In Greenleaf's study, teachers were asked to submit sample lesson materials and student work. The study supports the validity and reliability of using assignment ratings as a proxy for classroom observation to indicate teachers' classroom practice quality (Greenleaf et al, 2010). In this study, we observed teachers' and students' use of the social networking site throughout the academic year and collected all assignments and each assignment's descriptions and/or directions provided on the site.…”
Section: Teacher Assignments and Student Sample Artifactsmentioning
confidence: 69%
“…Therefore, we triangulated the data by analyzing teachers' assignments and students' sample artifacts to investigate their enactment of the cognitive tools approach. Using teacher classroom assignments as an indicator to measure their practices is reported in the literature (Clare, 2000;Greenleaf et al, 2010.) In Greenleaf's study, teachers were asked to submit sample lesson materials and student work.…”
Section: Teacher Assignments and Student Sample Artifactsmentioning
confidence: 99%